Prinzipien der botanischen Nomenklatur in der Renaissance - Selosse, Philippe (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The aim of this paper is to bring to light the pattern underlying botanical nomenclature in the Renaissance. The analysis shows that this nomenclature was conceived within the framework of the Renaissance episteme, i.e. within a logical and religious framework and that it is characterized by a threefold purpose: the appellations must give an essential definition of plants, reflect the classification of the botanists, and be easy to remember , that is, they must be short. Consequently, the nomenclature is structured by various principles: philosophical (logical division), linguistic (anaphora, polysemy) and cognitive (typicality). Finally, the analysis leads to a definition of the concept of ‘nomenclature’ in the Renaissance.